2017
DOI: 10.3847/1538-4357/836/1/24
|View full text |Cite
|
Sign up to set email alerts
|

JET Formation in Solar Atmosphere Due to Magnetic Reconnection

Abstract: Using numerical simulations, we show that jets with features of type II spicules and cold coronal jets corresponding to temperatures 10 4 K can be formed due to magnetic reconnection in a scenario in presence of magnetic resistivity. For this we model the low chromosphere-corona region using the C7 equilibrium solar atmosphere model and assuming Resistive MHD rules the dynamics of the plasma. The magnetic filed configurations we analyze correspond to two neighboring loops with opposite polarity. The separation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…The shock-transition region interaction is slightly modified by the existence of the magnetic field in the magneto-acoustic shock wave (Hollweg et al 1982). Magnetic reconnection has also been suggested as an energy source for acoustic wave generation (Uchida 1969;Pikel'ner 1969Pikel'ner , 1971Heggland et al 2009;Singh et al 2011;González-Avilés et al 2017). The magnetic reconnection model has the advantage of chromospheric jets being accelerated by both the shock wave and the Lorentz force (Takasao et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The shock-transition region interaction is slightly modified by the existence of the magnetic field in the magneto-acoustic shock wave (Hollweg et al 1982). Magnetic reconnection has also been suggested as an energy source for acoustic wave generation (Uchida 1969;Pikel'ner 1969Pikel'ner , 1971Heggland et al 2009;Singh et al 2011;González-Avilés et al 2017). The magnetic reconnection model has the advantage of chromospheric jets being accelerated by both the shock wave and the Lorentz force (Takasao et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We calculate this numerical solution using a High Resolution Shock Capturing method, with a method of lines that uses the Harten-Lax-van Leer-Einfeldt flux formula, minmod reconstructor and third order Runge-Kutta time integrator (see for instance [8,9,10] for some applications). …”
Section: Generation Of the Signalmentioning
confidence: 99%
“…Type I spicules are suggested to be shock-driven and have lifetimes on the order of 3-7m i n u t e s (De Pontieu et al 2004 ) structures that are thought to form due to reconnection (e.g., de Pontieu et al 2007;Rouppe van der Voort et al 2009;González-Avilés et al 2017a).T h i s classification into two classes is controversial since spicules are multithermal and traverse multiple wavelengths (Zhang et al 2012;Pereira et al 2014). Spicules have been observed to separate into smaller magnetic substructures (Sterling et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Observations by Skogsrud et al (2014) imply that spicules are multithreaded. Analytical and numerical modeling has found that spicules (and spicule-type structures) can be driven in a number of ways, including magnetohydrodynamic (MHD) turbulence (Cranmer & Woolsey 2015), p-modes (De Pontieu et al 2004;Martínez-Sykora et al 2009), shock rebounds (Hollweg 1982;M u r a w s k i&Z a q a r a s h v i l i2010), magnetic reconnection (González-Avilés et al 2017a, 2017b, and granular buffeting (Roberts 1979).…”
Section: Introductionmentioning
confidence: 99%